SISTEM PENGENDALIAN MANAJEMEN LINTAS BUDAYA: STUDI KASUSPADARESTORAN “T”DI SURABAYA - Felicia Lianggara; Bonnie Soeherman (Perpustakaan Universitas Surabaya, 2018)
This study was made to look at management control systems, acculturation, and cross-cultural communication barriers that appear in Restaurant